Michelangelo & Sebastiano - Wivel, Matthias (National Gallery Company, 2017)
The first publication to consider the relationship between these two major artists of the High Renaissance. Through most of Michelangelo's working life, one of his closest colleagues was the great Venetian painter Sebastiano del Piombo (1485--1541). The two men met in Rome in 1511, shortly after Sebastiano's arrival from his native city, and while Michelangelo was based in Florence from 1516 to 1534 Sebastiano remained one of his Roman confidants, painting several works after partial designs by him. This landmark publication is about the artists' extraordinary professional alliance and the friendship that underpinned it. It situates them in the dramatic context of their time, tracing their evolving artistic relationship through more than three decades of creative dialogue. Matthias Wivel and other leading scholars investigate Michelangelo's profound influence on Sebastiano and the Venetian artist's highly original interpretation of his friend's formal and thematic concerns. The lavishly illustrated text examines their shared preoccupation with the depiction of death and resurrection, primarily in the life of Christ, through a close analysis of drawings, paintings, and sculpture. The book also brings the austerely beautiful work of Sebastiano to a new audience, offering a reappraisal of this less famous but most accomplished artist
Keywords: Michelangelo -- Buonarroti -- 1475-1564; Del Piombo, Sebastiano -- 1485-1547; Italien; Michelangelo Buonarroti 1475-1564 / Exhibitions; Sebastiano 1485-1547 / Exhibitions; Art, Renaissance / Exhibitions / Italy; Ausstellungskatalog; Ausstellungskatalog -- The National Gallery -- 15.03.2017-25.06.2017 -- London